THE SECRET ASSOCIATION OF HOTELS AND CULTURE - Kulcsár, Erika; Farkas, Ottó (Revista de turism - studii și cercetări în turism, 2018)
Culture appears as one (if not the most important) of the influencing factors of consumer behavior in the literature. As it recently can be experienced we are members of a service-based society. Thus, services are valorized and have an increasingly important role in our lives, since today's consumers act as warriors in the pursuit of endless experiences. However, according to some opinion, cultures are merging continuously, and today they are leading towards an emerging global culture. According to this statement, the question arises whether culture can be considered an important factor influencing the consumers of tourism services. The purpose of this paper is to investigate the role of culture and to examine the intensity of the classical and extended marketing mix elements at the Hilton Prague Hotel.